The development of Active Management Model to approach the Special Needs Children in Educational Promoting Efficiency Network of Special Education Centre Network 9 - Khueawan, Tharika; Nuntee, Sakdinaporn; Prommuangkhun, Sukhum (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purposes of the study were: 1) Study the current desirable conditions and needs to develop proactive management to reach children with special needs. of the network to promote the efficiency of education management Center for Special Education, Network 9 2) Develop a proactive management model and 3) Evaluate the proactive management model. The findings were as follows: The present condition consists of 3 components: present condition, desirable condition, and necessary needs Overall, it was at a high level in all aspects. In terms of the requirements component, Required is the highest order. 2) Develop a proactive management model for accessing children with special needs, found that 2.1) inputs 2.2) process 2.3) outcome teachers who have been developed to have knowledge that meets the special needs of each individual. Using a proactive management process using PDCA principles and productivity is a look at where the child ends up and where does the next. 3) The most appropriate and useful model was purpose, followed by principle and reason. service unit model and rehabilitation of the disabled by the community by the Conditions for Success Management according to the Quality Cycle Concept (PDCA).